Mechanical Property Characterization of Architectural Coated Woven Fabrics Subjected to Freeze–Thaw Cycles - Hastia Asadi; Joerg Uhlemann; Natalie Stranghoener; Mathias Ulbricht (Textiles, 2024)
This paper presents experimental investigations into the freeze–thaw response of two common architectural coated woven fabrics. Strip specimens for the tensile tests were exposed to −20 °C for three hours followed by three hours of thaw at ambient temperatures. This was repeated for a maximum of 100 cycles. Afterwards, the residual tensile strength was measured and compared to results achieved for test specimens without prior freeze–thaw cycles. Maximum mean tensile strength reductions of approximately 21% (warp direction) and 19% (weft direction) for probed polytetrafluoroethylene (PTFE)-coated woven glass fiber fabrics were identified, while no remarkable tensile strength deterioration rate was observed for the investigated polyvinyl chloride-coated woven polyethylene terephthalate materials. Overall, the results indicate that freeze–thaw cycles can have a significant deteriorating impact on the mechanical properties of glass-PTFE fabrics.